PEMBERDAYAAN SISWA SEKOLAH DASAR MELALUI INOVASI PERMEN HERBAL DAN WIRAUSAHA KREATIF - Indrawati, Lilik; Priskila, Onny; Longdong, Secillia Shevani Prilia; Sepungan, Maria Indah Lestari (Universitas katolik Musi Charitas, 2025)
Purpose: This community service activity was designed to enhance health literacy based on herbal plants and to foster creative entrepreneurial interest among elementary school students through an innovation in herbal candy production. Design/Methodology/Approach: A service learning approach was employed by integrating conceptual learning on herbal plants, hands-on practice in producing herbal candy made from turmeric and tamarind, and learning evaluation through pretests, posttests, and entrepreneurial interest questionnaires. The activity involved fifth- and sixth-grade students of YBPK Christian Elementary School, Surabaya. Findings: The results indicated an improvement in participants’ understanding of the types and benefits of herbal plants, as well as the basic stages of herbal candy production. In addition, more than half of the participants demonstrated an initial interest in developing herbal-based products as simple entrepreneurial opportunities. Practical Implications: Herbal candy products show potential as healthier snack alternatives and as an educational medium for introducing entrepreneurship grounded in local wisdom at the elementary school level. Originality/Value: This activity integrates health education and creative entrepreneurship based on herbal plants into practical learning experiences, offering an applicable and replicable community service model for elementary school education.